2017
DOI: 10.1002/jbmr.3143
|View full text |Cite
|
Sign up to set email alerts
|

BPS804 Anti-Sclerostin Antibody in Adults With Moderate Osteogenesis Imperfecta: Results of a Randomized Phase 2a Trial

Abstract: This 21-week, open-label, phase 2a trial aimed to evaluate the pharmacodynamics and safety of multiple, escalating infusions of BPS804, a neutralizing, anti-sclerostin antibody, in adults with moderate osteogenesis imperfecta (OI). Patients received BPS804 (three escalating doses each separated by 2 weeks [5, 10, and 20 mg/kg]) or no treatment (reference group). The primary efficacy endpoints were mean changes from baseline to day 43 in: procollagen type 1 N-terminal propeptide (P1NP), procollagen type 1 C-ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
87
0
9

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 129 publications
(97 citation statements)
references
References 35 publications
1
87
0
9
Order By: Relevance
“…40 Moreover, SOST antibodies increase osteoclast numbers and stimulate the bone formation rate in a mouse model of recessive osteogenesis imperfect (OI) and in adults with moderate OI from a randomized phase 2a trial. 41,42 In this study, we demonstrated that SOST negatively regulated osteogenesis in EMSCs, which are the progenitors of all tooth tissues, suggesting that targeting SOST may have great prospects in dental tissue regeneration and engineering.…”
Section: Cohen-kfir Et Al Have Demonstrated That Sirt1 Negatively Regmentioning
confidence: 74%
See 2 more Smart Citations
“…40 Moreover, SOST antibodies increase osteoclast numbers and stimulate the bone formation rate in a mouse model of recessive osteogenesis imperfect (OI) and in adults with moderate OI from a randomized phase 2a trial. 41,42 In this study, we demonstrated that SOST negatively regulated osteogenesis in EMSCs, which are the progenitors of all tooth tissues, suggesting that targeting SOST may have great prospects in dental tissue regeneration and engineering.…”
Section: Cohen-kfir Et Al Have Demonstrated That Sirt1 Negatively Regmentioning
confidence: 74%
“…SOST is a vital negative regulator of bone formation. It has recently been reported that SOST inhibition increases bone formation in several disorders . Delgado‐Calle et al have shown that SOST inhibition augmented osteoblast numbers, promoted new bone formation and decreased osteoclast number in multiple myeloma‐colonized bone .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, treatment with SclAb not only stimulated bone mass in WT and Ts65Dn DS mice but also returned bone mass and bone microarchitecture to normal age‐matched WT levels at multiple skeletal sites. The data suggest that the anabolic effect of SclAb treatment that is well documented in high bone turnover scenarios such as osteoporosis and osteogenesis imperfecta was able to enhance bone mass, bone quality, and bone formation in the face of low bone turnover. The microarchitectural changes in the trabecular and cortical compartments are entirely consistent with increased bone strength after SclAb treatment, although this was not specifically assessed.…”
Section: Discussionmentioning
confidence: 85%
“…However, unlike PTH, there is little data to suggest that SclAb therapy would be inappropriate for the treatment of low bone mass in people with DS. Indeed, there is data from a recent randomized phase 2a clinical trial in adults with moderate osteogenesis imperfecta that demonstrated safe and powerful anabolic effects in a younger adult population than previous SclAb clinical trials. In contrast, there is conflicting data in a preclinical murine model of severe osteogenesis imperfecta suggesting that SclAb treatment may be less effective in more severely affected osteogenesis imperfecta mice .…”
Section: Discussionmentioning
confidence: 99%